The Alcohol Deprivation Effect: Marked Inhibition by Anticatalase Gene Administration into the Ventral Tegmental Area in Rats. (25th March 2013) - Tampier, Lutske; Quintanilla, María Elena; Karahanian, Eduardo; Rivera‐Meza, Mario; Herrera‐Marschitz, Mario; Israel, Yedy
Abstract : Background: Animals that have chronically consumed alcohol and are subsequently deprived of it markedly increase their intake above basal levels when access to alcohol is reinstated. Such an effect, termed the alcohol deprivation effect (ADE), has been proposed to reflect (i) an obsessive–compulsive behavior, (ii) craving, or (iii) an increased reinforcing value of ethanol (EtOH). It has been reported that acetaldehyde, a highly reinforcing metabolite of EtOH, is generated in the brain by the action of catalase. Recent studies show that the administration of an anticatalase (shRNA)‐encoding lentiviral vector into the brain ventral tegmental area (VTA) of naïve rats virtually abolishes (85 to 95%) their EtOH intake. It is hypothesized that the antireinforcing effect of the anticatalase vector will also inhibit the ADE. Methods: Two‐month‐old Wistar‐derived UChB alcohol drinker rats were offered free access to water and 10 and 20% EtOH for 67 days. Thereafter, the animals were deprived of EtOH for 15 days and were subsequently offered access to the EtOH solutions. At the start of the deprivation period, animals were microinjected a single dose of an anticatalase (or control) vector into the VTA. EtOH intake was measured on the first hour of EtOH re‐exposure as well as on a 24‐hour basis for 7 days. Results: A marked ADE was observed when EtOH intake was measured on the first hour or 24 hours following EtOH re‐exposure, compared to the corresponding controls. The administration of the anticatalase vector reduced ADE by 60 to 80% ( p  < 0.001) on the first hour and by 63 to 80% ( p  < 0.001) on the initial 24 hours of EtOH re‐exposure (first and second ADE, respectively) without changing the total fluid intake, indicating a specific effect on EtOH drinking. Conclusions: Ethanol intake associated with ADE—a binge‐like drinking behavior—is markedly inhibited by the administration of an anticatalase vector into the VTA, which blocks the conversion of EtOH into acetaldehyde, strongly suggesting that the marked increased EtOH intake that follows an alcohol deprivation period is mediated by acetaldehyde and its reinforcing metabolite.